2019
DOI: 10.1136/bmjopen-2019-031161
|View full text |Cite
|
Sign up to set email alerts
|

Social media use and adolescent sleep patterns: cross-sectional findings from the UK millennium cohort study

Abstract: ObjectivesThis study examines associations between social media use and multiple sleep parameters in a large representative adolescent sample, controlling for a wide range of covariates.DesignThe authors used cross-sectional data from the Millennium Cohort Study, a large nationally representative UK birth cohort study.ParticipantsData from 11 872 adolescents (aged 13–15 years) were used in analyses.MethodsSix self-reported sleep parameters captured sleep timing and quality: sleep onset and wake times (on schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
87
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(96 citation statements)
references
References 50 publications
5
87
2
2
Order By: Relevance
“…Our findings are contrary to previous studies in the field that have reported associations between increased bedtime social media use and poorer affective and mental wellbeing (Burke et al, 2010; Lin et al, 2016; Primack et al, 2017; Sagioglou & Greitemeyer, 2014), and between social media use and poor sleep (Lemola et al, 2015; Levenson et al, 2017; Scott et al, 2019). Important distinctions between our study and previous research might account for these dissimilarities.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our findings are contrary to previous studies in the field that have reported associations between increased bedtime social media use and poorer affective and mental wellbeing (Burke et al, 2010; Lin et al, 2016; Primack et al, 2017; Sagioglou & Greitemeyer, 2014), and between social media use and poor sleep (Lemola et al, 2015; Levenson et al, 2017; Scott et al, 2019). Important distinctions between our study and previous research might account for these dissimilarities.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies examining the link between social media use and sleep have reported that increased use of social media, specifically before sleep, is associated with poorer sleep patterns. In a recent study using data from the Millennium Cohort Study on individuals aged between 13–15 years in the UK, Scott et al (2019) found that longer time spent on social media during the day was associated with later sleep times and later wake up times on school days, as well as difficulty falling back asleep after night‐time awakening. Studies also report that increased social media use at night before sleep is associated with more sleep disturbances (Levenson et al, 2016, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter difference corresponds to an interesting daily peak of highest activity at 9 PM which occurs in both cohorts. This peak of activity levels may correspond to a period of time after dinner and before bedtime which individuals use for recreational social media use 49 . Since this peak is more pronounced for the D cohort, it raises the interesting possibility that social media use is partly involved in altering the circadian activity levels of the D cohort.…”
Section: Category ( C X )mentioning
confidence: 99%
“…Finally, social media, regardless of its utility as data sources for social science [52][53][54][55] , has become an important factor in the social lives of billions of individuals. The analysis of social media and related mobile communication data might therefore shed light on how or whether these platforms affect public health at a global scale 34,49,56 .…”
Section: Category ( C X )mentioning
confidence: 99%